소득이 산후우울에 미치는 영향에서 사회적 지지의 조절효과: 모성건강불평등을 중심으로 - 최인선(Insun Choi); 이소영(So-Young Lee) (보건교육건강증진학회지, 2023)
Objectives: This study primarily aimed to determine the level of inequality in maternal health by identifying the effect of income on postpartum depression and examining whether social support is effective in alleviating maternal health inequality. Methods: Multiple regression analysis using a moderating effect model was conducted to analyze data from a nationwide sample of 3,127 pregnant women in Korea using the 2021 Postpartum Care Survey. Results: Income had a significant effect on postpartum depression. “Social support,” including “Experience with social support” and “Family support,” was found to have a statistically significant effect in alleviating maternal health inequalities. Conclusion: This study found that although there may be inequalities in postpartum depression depending on income, maternal health inequalities can be alleviated if sufficient social support is provided. First, to increase family support, postpartum depression must be reduced through spousal education. Second, if support is not available within the family, the expecting mothers should have access to a support system within the community. Third, if social support is provided as a policy target, it can effectively alleviate maternal health inequalities. Fourth, there is a need to strengthen and promote policies with socially supportive characteristics to mitigate disparities in postpartum depression and effectively alleviate maternal health inequalities KCI Citation Count: 0